A great research lab on University History and Higher Education in Spain: Instituto Antonio de Nebrija de Estudios sobre la Universidad (1997-2009) - Pomante, Luigiaurelio (Historia de las Universidades, 2017)
This volume reconstructs with great detail the history and the rapid development of the prestigious research centre, Instituto Antonio de Nebrija de Estudios sobre la Universidad, founded in the late 1980s at Charles III University of Madrid and briefly risen to a truly great international research lab on University and Higher Education History in Spain and in South-American countries. On the basis of a wide range of archival and print sources, the author puts his focus on the most significant moments of the Instituto Antonio de Nebrija de Estudios sobre la Universidad, from its laborious creation in 1997 to the attempt to convert it into a LOU University Institute for Research and its incorporation into the Instituto Figuerola de Historia y Ciencias Sociales in 2009, and he introduces the countless and considerable scientific research activities promoted over the years, without leaving out that seriousness and that methodological rigour which have punctually characterized all the works produced and the initiatives made.